Augustine, the Disciplines, and Varro’s Disciplinarum libri - D’Anselmi, Luca A. (Augustinianum, 2024)
In this article, I challenge Shanzer’s treatment of the relationship between Varro’s Disciplinarum libri and Augustine’s early disciplinary project, in which she argued that «squeamishness» with the personifications that supposedly characterized Varro’s disc. caused Augustine to abandon the disciplines. I consequently outline a more plausible view of the development of Augustine’s thought. He did not abandon the disciplines or become «hostile» to them in his later career, as Shanzer and others have concluded. Instead, he reoriented them towards the study of Scripture, while maintaining the importance of a truly liberal education in pursuit of the knowledge of God.